2003
DOI: 10.1128/jvi.77.11.6562-6566.2003
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Cross-Reactivity of CD4+Adenovirus-Specific T Cells: Implications for Immunotherapy and Gene Therapy

Abstract: A, B, and C). This cross-reactivity of Ad-specific T cells has relevance both for Ad-based gene therapy protocols, as well as for the feasibility of T-cell-mediated adoptive immunotherapy in recipients of an allogeneic stem cell transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 45 publications
4
74
0
Order By: Relevance
“…Various research groups are currently investigating the role of CD4 þ and CD8 þ T cells in the cellular immune response to HAdV. 23,[25][26][27] Together with a more detailed analysis of the origin of the infectious HAdV in the setting of allogeneic SCT and of the HAdV type(s) infecting a patient, this research will certainly enhance our knowledge of the interaction between HAdV and the immune system. This will be of benefit not only for recipients of stem cell grafts but also for recipients of solid organ transplants and other immunocompromised patients in which HAdV infection may have serious complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various research groups are currently investigating the role of CD4 þ and CD8 þ T cells in the cellular immune response to HAdV. 23,[25][26][27] Together with a more detailed analysis of the origin of the infectious HAdV in the setting of allogeneic SCT and of the HAdV type(s) infecting a patient, this research will certainly enhance our knowledge of the interaction between HAdV and the immune system. This will be of benefit not only for recipients of stem cell grafts but also for recipients of solid organ transplants and other immunocompromised patients in which HAdV infection may have serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Since HAdV-specific T cells generated against HAdV serotype 5 are crossreactive to HAdV serotypes from the same or even other species, this approach may be feasible. 23 Recent work from our group has shown that HAdV-specific T cells, devoid of alloreactivity, can be generated using methylene blueinactivated whole virus. 23 To circumvent the preparation of GMP-compatible virus batches, a number of conserved peptides derived from HAdV 5 hexon has been identified that are recognized by T cells from the majority of adult blood bank donors.…”
Section: Immunotherapy For Hadv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Authors generated with group C adenovirus have been shown to exert distinct crossreactivity patterns, recognising HAdV serotypes from the three subgroups A, B, and C (Heemskerk et al, 2003). A serotype-independent reactivity in patients post-SCT against the HAdV-antigen used for detection and isolation, indicate crossreactive viral epitopes in the antigen (Feuchtinger et al, 2004(Feuchtinger et al, , 2005.…”
Section: T Feuchtinger Et Al ª 2006mentioning
confidence: 99%
“…This was complicated by the fact that the minimal sequence recognized was not defined definitively in all studies. We used the likely minimal sequence of peptides characterized in this study, as shown in Table 1 in bold, underlined and italic, with peptides to the level identified by other groups Heemskerk et al, 2003Heemskerk et al, , 2006Leen et al, 2004bOnion et al, 2007;Tang et al, 2006). Because we used 15-mers, compared with 20-or 30-mers used by others for peptide identification, the sequences containing the minimal peptides could be narrowed in several cases.…”
Section: Location Of Peptides Identified In This and Other Published mentioning
confidence: 99%